Continuity of mental health care during the transition from prison to the community following brief periods of imprisonment - Browne, Christie C.; Korobanova, Daria; Chemjong, Prabin; Harris, Anthony W. F.; Glozier, Nick; Basson, John; Spencer, Sarah-Jane; Dean, Kimberlie (Frontiers in Psychiatry, 2022)
Purpose - The prison-to-community transition period is one of high risk and need, particularly for those with mental illness. Some individuals cycle in and out of prison for short periods with little opportunity for mental health stabilization or service planning in prison or the community. This study describes the socio-demographic, clinical and criminal justice characteristics of individuals with mental illness and frequent, brief periods of imprisonment, examines continuity of mental health care between prison and the community for this group, and reports on post-release mental health and reoffending outcomes. Design/Methodology/Approach - This study examined a sample of 275 men who had recently entered prison in New South Wales (NSW), Australia, who had been charged with relatively minor offences and had been identified as having significant mental health needs. Baseline demographic and mental health information was collected via interview and file review and contacts with the prison mental health service were recorded for the period of incarceration. Follow-up interviews were conducted three months post-release to determine level of health service contact and mental health symptoms. Information on criminal justice contact during the three month period was also collected. Findings - The majority (85.5%) of the sample had contact with a mental health professional during their period of incarceration. Mental health discharge planning was, however, lacking, with only one in twenty receiving a referral to a community mental health team (CMHT) and one in eight being referred for any kind of mental health follow-up. Of those followed up three months post-release (n = 113), 14.2% had had contact with a CMHT. Of those released for at least three months (n = 255), one-third had received new charges in this period and one-fifth had been reincarcerated. Conclusion - Continuity of mental health care for those exiting prison is poor, particularly for those with mental health needs experiencing brief periods of imprisonment, and rates of CMHT contact are low in the immediate post-release period. These findings suggest a need for early identification of individuals in this group for timely commencement of intervention and release planning, and opportunities for diversion should be utilized where possible.